EFFECT OF YOGIC PRACTICES WITH AND WITHOUT WALKING ON SELECTED PSYCHOLOGICAL VARIABLE AMONG WOMEN SENIOR CITIZENS - Vasudevan, P. Sanmugapriya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Old Age is a natural part of the life cycle. All living organism including humans undergo the process from conception to infancy, child hood puberty, maturity and senescence. Longer life means more frailty and more disability. Apart from economic problem they face in their life, the common diseases like ortho, visual, audio and mental some face grave diseases of heart, blood etc. The care of old people in a separate branch of medicine called Geriatrics and scientific study of old age and process of growing old is called Gerontology. The definition of ageing varies from society to society and has been modified considerably over time. The purpose of this study was to find out the effect of Yogic practices with and without Walking on selected Psychological variable in Women senior citizens. The selected subjects 45 were randomly divided into three groups equally of which experimental Group – I underwent yogic practices with Walking, Group – II underwent yogic practices without Walking Group – II acted as Control Group. The subjects selected for this study were in the age group of above 60 years. Each group consisting of fifteen subjects, there experimental group as Group I & II and Control group as Group III. The following psychological variable was selected as dependent variables such as stress and the stress questionnaire constructed by Dr.Latha Satish (1997) consisting of 52 questions. , and the following variable was selected as independent variable as yogic practices and walking. The data collected on selected criterion variables were subjected to statistical analysis using analysis of covariance (ANCOVA) to find out any significant difference between the three groups on stress.